The Influence of Competence, Workload, and Work Environment on the Performance of Guidance and Counseling Teachers/Counselors with Work Motivation as an Intervening Variable at Public High Schools, SMK, MA in West Jakarta - Cahyaningsih, Puspita; Parwoto Parwoto (Dinasti Publisher, 2023)
Through work motivation as an intervening variable, this study aims to find out how Competence, workload, and work environment affect the performance of guidance and counseling (BK)/counselor teachers at public high schools, vocational schools, and MA in West Jakarta. The population and sample comprised 94 guidance and counseling teachers/counselors from public high schools, vocational schools, and Islamic high schools in West Jakarta. The results showed that Competence, workload, and work environment affect work motivation. The variable that has the most significant influence on the work motivation of counseling teachers is Competence in the Professional Competence dimension based on the indicator of implementing a comprehensive counseling work program. The variable that has the most significant influence on the performance of counseling teachers is the Work Environment from the Physical Work Environment dimension based on the workplace building indicator. Workload negatively affects the performance of counseling teachers but is not significant. Work motivation partially mediates Competence in influencing the performance of counseling teachers/counselors and partially mediates the work environment in influencing the performance of counseling teachers/counselors. In contrast, work motivation cannot mediate workload on the performance of counseling teachers.